O princípio da proibição de retrocesso social na Constituição Brasileira : sede material, aplicação e limites - Tatsch, Ricardo Luís Lenz (2017)
In a globalized society, which is in an accelerated and constant modification, social rights, more than ever, are being object of permanent attacks. On the other hand, we see an increasingly use the principle of irreversibility of social conquests in Brazilian law and for this reason we need to show where your seat material on brazilian Constitution of 1988, as well as how to give your use. Thus, we defend the principle of irreversibility of social conquests as a principle implied that arises from the proper structure of the social rights provided in the Constitution. And when we use it, the principles of reliable protection and the prohibition of discrimination must help, which should not have been violated by the rule or act that caused the social setback, beyond the criterion of proportionality and required the preservation of the essential core of fundamental right involved and the existential minimum.